South Sudan Economic Monitor, February 2022 : Towards a Jobs Agenda - World Bank (World Bank, Washington, DC, 2022)
South Sudan faced significant headwinds in FY2020/21, with the pandemic, floods, and violence flareups affecting economic activities. Consequently, the economy is estimated to have contracted by 5.4 percent in FY2020/21. Oil production declined by 5.9 percent as floods affected production and the COVID-19 pandemic delayed new investments to replace exhausted wells. In the agriculture sector, flooding precipitated estimated losses of 38,000 tons of cereals (4.3% of 2020 production) and 800,000 livestock according to FAO estimates. The overall cereal deficit was projected to reach 465,610 metric tons in 2021, equivalent to about 35 percent of the overall food requirement for the year, sustaining high levels of food insecurity. Living conditions continue to be impacted by violence, displacement, and inadequate access to basic services. With improving macroeconomic conditions supported by an ongoing macro-fiscal reform program, a modest growth rebound of 1.2 percent is projected in FY2021/22. Nevertheless, poverty levels are expected to remain exceptionally high. As the economy recovers from multiple shocks, a focus on policy options to stimulate the creation of a sufficient number of quality jobs to absorb a young and expanding labor force should take center stage. Economies that create jobs, particularly for the youth, are generally more stable and can elevate public confidence in the Government’s capacity to deliver. In South Sudan, an effective jobs support program would invest in immediate livelihood support, the recovery of modest business activities, and the revival of markets.